2020
DOI: 10.3390/su12208554
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Power: Reimagining Hospitals as Sustainable Energy Hubs

Abstract: Human health is a key pillar of modern conceptions of sustainability. Humanity pays a considerable price for its dependence on fossil-fueled energy systems, which must be addressed for sustainable urban development. Public hospitals are focal points for communities and have an opportunity to lead the transition to renewable energy. We have reimagined the healthcare energy ecosystem with sustainable technologies to transform hospitals into networked clean energy hubs. In this concept design, hydrogen is used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
10
0
1
Order By: Relevance
“…They mentioned that the heat produced by the solar thermal systems varied between 263-433 KWh/m 2 of the solar mirror while the seasonal coefficient of performance of the heat pumps varied between 2.42-2.61. Gurieff et al, 2020 have examined the possibility of creating energy hubs in community hospitals. The authors stated that public hospitals consume large amounts of energy while they have the opportunity to lead the transition to renewable energy.…”
Section: Use Of Low Carbon Technologies In Hospitalsmentioning
confidence: 99%
See 1 more Smart Citation
“…They mentioned that the heat produced by the solar thermal systems varied between 263-433 KWh/m 2 of the solar mirror while the seasonal coefficient of performance of the heat pumps varied between 2.42-2.61. Gurieff et al, 2020 have examined the possibility of creating energy hubs in community hospitals. The authors stated that public hospitals consume large amounts of energy while they have the opportunity to lead the transition to renewable energy.…”
Section: Use Of Low Carbon Technologies In Hospitalsmentioning
confidence: 99%
“…Our work is focused on the investigation of using several sustainable energy technologies covering the energy requirements in hospitals and zeroing their net-carbon emissions due to energy use . These clean energy technologies include energy saving technologies, renewable energy technologies as well as low carbon emission technologies (CADDET, 1977, Franco et al, 2017, Gurieff et al, 2020. The possibility of using several financial mechanisms for supporting the clean energy investments in hospitals is also studied.…”
Section: Introduction Journal Of Environment and Ecologymentioning
confidence: 99%
“…The results showed that the expected decrease in the battery prices will improve the resilience of RES when combined with BESS in applications that need high reliability like hospitals in islanded mode. Hospitals as a critical and resilient facility within the public sector facilities can be a leader for the development of flexible demand in the transition to higher shares of RES, and can provide innovation and learning for BESS as a new energy technology in the public sector [32]. The integration of RES with flow batteries is considered to replace backup combustion generators that are used to provide emergency power, to enhance the security of supply, and to convert hospitals from energy sinks to healthy and reliable energy resources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The application of gas engines for the improvement of the energy supply to hospitals has a decade-long history in Hungary, with both successful and less successful solutions. In the present market environment, and based on the significant (both electric and heatside) energy demands of hospitals (Erdélyi, A., Pulay Gy., 2021), as well as the special distribution of this demand in time, a service package that offers a solution for the provision of essential, continuously available, reliable and quality energy supply (Elekes, A., 2018) may completely transform the present system of relations between hospitals and energy suppliers, creating an arrangement that is successful for both parties (Gurieff, N., Green, D., Koskinen, I., et al, 2020). Another reason why this research is particularly timely is the fact that the majority of the combined gas engine production units established for the KÁP/KÁT (mandatory takeover support, earlier KÁP) electricity sale, which was fairly widespread in the 2000s, have been technically fully amortised, moreover, the heat supply contracts of hospitals are close to expiry or already expired, and they are extended only temporarily with the present equipment and service provider.…”
mentioning
confidence: 99%